Elucidation of the Dual Role of Mycobacterial MoeZR in Molybdenum Cofactor Biosynthesis and Cysteine Biosynthesis - Voss, Martin (Public Library of Science, 2011)
The pathway of molybdenum cofactor biosynthesis has been studied in detail by using proteins from Mycobacterium species, which contain several homologs associated with the first steps of Moco biosynthesis. While all Mycobacteria species contain a MoeZR, only some strains have acquired an additional homolog, MoeBR, by horizontal gene transfer. The role of MoeBR and MoeZR was studied in detail for the interaction with the two MoaD-homologs involved in Moco biosynthesis, MoaD1 and MoaD2, in addition to the CysO protein involved in cysteine biosynthesis. We show that both proteins have a role in Moco biosynthesis, while only MoeZR, but not MoeBR, has an additional role in cysteine biosynthesis. MoeZR and MoeBR were able to complement an E. coli moeB mutant strain, but only in conjunction with the Mycobacterial MoaD1 or MoaD2 proteins. Both proteins were able to sulfurate MoaD1 and MoaD2 in vivo, while only MoeZR additionally transferred the sulfur to CysO. Our in vivo studies show that Mycobacteria have acquired several homologs to maintain Moco biosynthesis. MoeZR has a dual role in Moco- and cysteine biosynthesis and is involved in the sulfuration of MoaD and CysO, whereas MoeBR only has a role in Moco biosynthesis, which is not an essential function for Mycobacteria.